Simulasi online taxi`s dispatch system dengan metode combinatorial optimization - Vincent Christian Andoko; Andreas Handojo; Henry Novianus Palit (Jurnal Infra, 2019)
Taxis are an important part of people's lives today. Taxis function as one of the means of public transportation that plays a role in serving the community in reaching the desired destination and is easily found because taxi services are available in most cities throughout the world. Following the development of technology, online taxis emerged. Online taxis are a means of public transportation using web or mobile based applications to connect passengers with taxis. Online taxis make it easy for passengers and taxis to find out the destination via an online map with GPS or the name of the desired destination and display important factors such as distance and duration quickly. Behind the features presented by online taxis, an optimal taxi dispatch method is needed. The road conditions in each area are different, for example traffic jams in the middle of the city are different from the traffic jams on the edge of the city. From these conditions it is not possible to use only one type of method for the taxi dispatch process in the entire area. By using simulations that have several methods, it can be determined which method is optimal for the area determined by giving an overview of the dispatch process by taxi along with the comparison of the results of the methods used in the simulation.The final result of this program is a simulation that can run 3 types of algorithms to pair taxis and passengers based on 3 factors, namely the duration, distance, and total passengers that each taxi has served. This simulation can provide a comparison of the results of the three algorithms and the calculation of the factors used in the same scenario to make it easier for users to determine the algorithm and calculation`s formula for the appropriate factors in a particular region and time.